Research progress on blood compatibility of hemoperfusion adsorbent materials - Zhang, Liangqing; Liu, Guohao; Xia, Qingping; Deng, Li (Frontiers in Bioengineering and Biotechnology, 2024)
This comprehensive review examines the latest developments in improving the blood compatibility of hemoperfusion adsorbents. By leveraging advanced coating and modification techniques, including albumin-collodion, cellulose, hydrogel, and heparin coatings, notable enhancements in blood compatibility have been achieved across diverse adsorbent types, such as carbon-based, resin-based, and polysaccharide-based materials. Despite promising laboratory results, the intricate manufacturing processes and elevated costs present significant challenges for broad clinical application. Therefore, future endeavors should focus on cost-benefit analysis, large-scale production strategies, in-depth exploration of blood-material interactions, and innovative technologies to propel the development of safer and more effective blood purification therapies.